Vivienda e informalidad urbana: el caso de Airbnb y sus posibles impactos en un distrito de Lima - Pérez Guerra, Joaquín (2023)
Recent studies have considered urban informality as a multidimensional problem, and have discussed whether it is really a deviation or externality of formality. The objective of this essay is to prove that Airbnb’s operation in Lima occurs in a rental market where private and state actors co-produce informality to satisfy their interests. First, the argument is presented that Airbnb exploits local conditions of informality in contexts of deregulation, as well as state ambiguity in order to facilitate accumulation processes. From this, secondly, it is argued that the presence of Airbnb has serious effects on the production of the city: urban investment, gentrification, construction and residentiality. To do this, the possible impact of Airbnb in the Barranco district is analyzed. It is concluded that: i) informality is a modus operandi of urban planning by the State and private actors, and that it is not separated from the formal system, and ii) that Airbnb activity has bidirectional effects on socio-spatial aspects. of the general rental market such as investment in urban housing, gentrification and residentiality. Attempting a more detailed understanding of the various dimensions of urban informality in Peru is an urgent exercise, especially if we consider that the phenomenon of informality is a recurring and primary concern in discussions about public and economic policies, as well as in deliberation policy.